Probing the Interfaces in Nanosilica‐Supported TiO2 Photocatalysts by Solid‐State NMR and In Situ FTIR. Issue 12 (12th October 2018) - Singh, Rustam; Bayal, Nisha; Maity, Ayan; Pradeep, D. Jeiyendira; Trébosc, Julien; Madhu, P. K.; Lafon, Olivier; Polshettiwar, Vivek
Abstract: Although the range of photocatalysts with controllable size, shape and morphology has developed in recent years with a large number of silica‐supported TiO2 catalysts, the details of photocatalytic interfaces between nanosilica and TiO2 them and the mechanisms of TiO2 functionalization of silica surfaces are not yet well understood. It is worth mentioning that the understanding of a mechanism from a molecular point of view has always been a challenge in the field of materials science. Here, we probe interfaces in (dendritic fibrous nano‐silica (DFNS) supported TiO2 photocatalysts as well as propose and prove the formation mechanism of the photocatalyst, DFNS/TiO2, by ammonia‐assisted functionalization of DFNS by titanium butoxide (TBOT). The proposed formation mechanism includes the following steps: i) the deprotonation of silica surface (silanols) by ammonia and the hydrolysis of TBOT to titanium hydroxide [Ti(OH)4 ], ii) the donation of electron lone pair from ammonia to the Ti 4+ ion of Ti(OH)4, iii) the release of hydroxide ions, followed by hetero‐condensation of dehydroxylated titanium ions with the deprotonated silanols, generating Si−O−Ti oxobridges, iv) the formation of oxy‐anion of titanols and its reaction with another molecule of ammonia‐activated titanium hydroxide to generate Ti−O−Ti oxobridges, and v) the continuation of the above cycle of steps until the titanium hydroxide precursor is consumed to produce silica supported titanium hydroxide. During thermal treatment, the titanols condense, yielding DFNS/TiO2 photocatalysts. To prove this mechanism, detailed solid‐state 1 H, 29 Si, 47, 49 Ti NMR and in situ FTIR studies were carried out, based on which different surface species formed during TiO2 growth on DFNS were identified. This has led to fundamental insights into the reaction of TBOT with DFNS silica surface and interfaces between DFNS and TiO2 . Abstract : The interfaces and formation mechanism of TiO2 photocatalysts supported by dendritic fibrous nanosilica (DFNS) are explored by using detailed solid‐state 1 H, 29 Si, 47, 49 Ti NMR and in situ FTIR studies. Different surface species formed during TiO2 growth on DFSN were identified, along with fundamental insights into the reaction of titanium butoxide with the DFNS silica surface and interfaces between DFNS and TiO2 .